Trends and Challenges in Digital Business Innovation - Morabito, Vincenzo. (Springer International Publishing : Imprint: Springer, 2014)
This book describes the trends in digital innovation that are of most importance for businesses and explores the key challenges. The book is in three parts, the first of which focuses on developments in digital systems. Here, the ever-growing relevance of big data, cloud computing, and mobile services for business is discussed, and detailed consideration is given to the importance of social listening for understanding user behavior and needs and the implications of IT consumerization. In the second part, trends in digital management are examined, with chapters devoted to work practice, digital business identity as well as branding and governance. The final part of the book presents and reviews case studies of digital innovation at the global level that provide a benchmark of best practices, with inclusion of instructive fact sheets. While the book offers academic coverage of the digital transformation of business organizations and the associated challenges, it also describes concrete, real-world issues in clear, easy-to-understand language and will serve as a toolbox for managers that can be readily consulted. The text is supported by informative illustrations and tables, and practitioners will also benefit from the reported case studies and highlighted insights and recommendations.